Pink esthetic treatment of gingival recession, black triangle, and gummy smile: a narrative review - Hyunkyung Kim; Sungtae Kim; Young-Dan Cho (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background With the increasing demand for comprehensive smile esthetics, pink esthetics—referring to the harmonious appearance of the gingival tissues—has gained significant attention. However, conditions such as gingival recession, black triangles, and gummy smiles can compromise these outcomes and remain challenging to manage with conventional surgical approaches. This study aimed to review minimally invasive and simplified approaches for pink esthetic enhancement using biomaterials such as collagen matrix, hyaluronic acid dermal fillers, and botulinum toxin. Main text The use of a collagen matrix for gingival phenotype modification has demonstrated effectiveness in achieving root coverage and increasing gingival thickness while offering a less invasive alternative to traditional surgical techniques. Interdental papilla loss—commonly referred to as the “black triangle”—remains difficult to correct using both surgical and restorative procedures; however, hyaluronic acid dermal fillers offer a promising solution for reconstructing interdental gingival architecture. Additionally, excessive gingival display (gummy smile) caused by hyperactivity of the upper lip elevator muscles can be efficiently managed with botulinum toxin injections, providing a nonsurgical option for improving smile esthetics. Conclusions The use of these biomaterials in pink esthetic management enables clinicians to achieve favorable esthetic outcomes with reduced invasiveness. This approach minimizes the need for additional restorative or surgical interventions, thereby enhancing patient comfort and satisfaction.